THEORETICAL APPROACH FOR THE GEOMETRICALLY NONLINEAR BUCKLING ANALYSIS OF SINUSOIDAL VELAROIDAL SHELLS - Светлана Львовна Шамбина (Structural Mechanics of Engineering Constructions and Buildings, 2017)
The main subjects of the article are theoretical strength and buckling analyses of a sinusoidal velaroidal shell subjected to its self-weight and uniformly distributed load in geometric nonlinearity. A short history of finite element applications to shell buckling is given. The finite element method is used in its matrix formulation. The elastic stiffness matrixes in the local coordinate system of the membrane element are defined in their general form. The out-of-plane geometric stiffness matrix for the plate along the same lines is derived.